2015
DOI: 10.2152/jmi.62.24
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the development of genetically encoded Ca<sup>2+ </sup>indicators

Abstract: GECIs are categorized into two groups based on the molecular design, i.e., two -FP based and single -FP based one as is discussed in many reviews (Table1, 2)(7, 8). REVIEW Recent progress in the development

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In contrast, much larger fluctuations of GCaMP3 fluorescence are seen in neonatal SCN cultured under similar conditions. Further studies using larger sample size and more sensitive reporters such as aequorin [ 69 ] or newer genetically encoded Ca 2+ indicators [ 76 ] may provide more secure evidence of circadian Ca 2+ oscillations in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, much larger fluctuations of GCaMP3 fluorescence are seen in neonatal SCN cultured under similar conditions. Further studies using larger sample size and more sensitive reporters such as aequorin [ 69 ] or newer genetically encoded Ca 2+ indicators [ 76 ] may provide more secure evidence of circadian Ca 2+ oscillations in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…For example RV caused an increase in Ca 2+ transients but RSV elevated [Ca 2+ ] c with few Ca 2+ transients until just prior to cell death, and PV infection disrupted the normal Ca 2+ oscillations of HeLa cells. Future studies using these GECI-expressing cell lines, as well as additional lines developed with other GECI varieties, will be able to further dissect the mechanisms by which viruses exploit ER Ca 2+ signaling (10, 22, 23). …”
Section: Discussionmentioning
confidence: 99%
“…In order to study both aspects of Ca 2+ signaling, a wide range of fluorescent Ca 2+ indicators have been developed to enable real time observations of changes in Ca 2+ levels [reviewed in (10)]. All Ca 2+ indicators are based upon fluorescent molecules that bind Ca 2+ ions and have different spectral properties between the Ca 2+ -free and the Ca 2+ -bound states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent developments of exogenous and in particular genetically encoded fluorescent indicators of neuronal activity such as GCaMP and YC-Nano have revolutionized the targeted expression of fluorescence with much higher signal levels. And even transgenetic lines exist [ 14 ]. Furthermore, recent work has shown that the dynamics of flavoprotein fluorescence can be optically mapped in wild-type CNS tissue as an indicator of oxidative metabolism [ 15 , 16 ], which might be also a useful tool in experimental stroke research.…”
Section: State-of-the-art Techniques To Study Neuronal Reorganizatmentioning
confidence: 99%